Communicating the Impact of Communication for Development : Recent Trends in Empirical Research - Inogaki, Nobuya (Washington, DC: World Bank, 2012)
The UN Millennium Development Goals call for not only greater financial commitment in international assistance programs but also innovative strategies to tackle the serious economic, health, education, and other basic human rights problems in the developing world. This paper is organized as follows: Chapter 2 is an overview of key theoretical models of development communication. Chapter 3 describes the characteristic patterns of recent empirical studies in development communication in terms of theoretical models and types of communication strategies. Chapter 4 presents some outstanding evidence of the impacts of communication on development initiatives. Chapter 5 discusses weak spots in the evidence. The concluding chapter will make suggestions for further research by drawing attention to the theoretical, methodological and empirical gaps in the existing academic research in development communication.